Extracellular matrix re-normalization to improve cold tumor penetration by oncolytic viruses - Soko, Geofrey F.; Kosgei, Benson K.; Meena, Stephene S.; Ng, Ying Jing; Liang, Huihui; Zhang, Bing; Liu, Qingjun; Xu, Tielong; Hou, Xinju; Han, Ray P. S. (Frontiers in Immunology, 2025)
Immunologically inert or cold tumors pose a substantial challenge to the effectiveness of immunotherapy. The use of oncolytic viruses (OVs) to induce immunogenic cell death (ICD) in tumor cells is a well-established strategy for initiating the cancer immunity cycle (CIC). This process promotes the trafficking and infiltration of CD8+ T cells into tumors, thereby eliciting a tumor-specific immune response. Despite the potential of OVs for handling cold tumors, clinical outcomes have fallen short of expectations. To better understand the obstacles faced by oncolytic virus immunotherapy (OVI), we would like to revisit the OV issue. Growing evidence indicates that limited intratumoral penetration and inadequate intratumoral distribution of OVs are critical factors contributing to the suboptimal response to OVI. Aberrant expressions of matrix proteins by cancer-associated fibroblasts (CAFs) alter the mechanical properties of the tumor extracellular matrix (ECM). This results in increased ECM desmoplasia and elevated intratumoral interstitial fluid pressure (IFP), creating physical barriers that impede the penetration and dissemination of OVs within tumors. This review explores the latest advancements in strategies designed to improve the intratumoral penetration of OVs to facilitate the penetration of tumor-infiltrating lymphocytes (TILs) into cold tumors. Additionally, we investigated current clinical trials and challenges associated with translating these strategies into clinical practice to improve patient outcomes.